Long-term results of patients with type 2 diabetes attending a multidisciplinary diabetes kidney disease clinic - Surendra Prasad Singh (Student's Journal of Health Research, 2023)
Background: Diabetic and chronic kidney disease together tend to worsen the outcomes. A newer approach to treat both the comorbid disease can slow down the prognosis of both the disease leading to quality of life. Aim: To evaluate the outcomes when the patients are treated simultaneously for chronic kidney disease and diabetes at a diabetic kidney disease clinic MethodS: The study was conducted amongst two group of patient. The first group had diabetes and chronic kidney diseases. Doctors treating the diabetes referred these patients to a diabetic kidney disease clinic. While the other group of patients were not treated at diabetic kidney disease center but they had comparable diabetes and chronic kidney disease. The prognosis was tracked in both the groups; the kidney of the patients was monitored if it had reach stage 5 kidney disease and the glomerular filtration rate was less than 1.5 milliliter per minute and per 1.73 m2. Result: During the follow up the reports of the patients were analyzed it was observed that the 49.4% patients had reached chronic kidney disease stage 5 who were treated at the diabetic kidney disease clinic. 55.5% of the patients of the patients not treated at diabetic kidney disease clinic reached the chronic kidney disease stage 5. When the difference was compared statistically it was found to be statistically significant. Conclusion: From this study it is concluded that when patients are treated for chronic kidney disease and diabetes simultaneously the prognosis towards the end stage kidney is delayed. When multidisciplinary clinics focus on the management of diabetes and kidney disease it can add years of quality life for the patients. Recommendation: Renin-angiotensin-aldosterone system inhibitors are strongly recommended for patients with diabetes, hypertension, and albuminuria.